Foundation of Accounting: an IFRS approach - Omolehinwa, Eddy .O (Lagos : Pumark Educational publishers, 2014)
The book is a contribution in the direction suggested by NASB. It does so not only by filling in part of the existing gap in the accounting literature that can be used to teach some aspects of IFRS. It should also be embraced in the teaching of a foundation course in Financial Accounting.
includes index
usc 07/06/17
Loans